Pandangan Imam Al-Ghazali Terhadap Pengambilan Keuntungan Dalam Kegiatan Jual Beli - Hendra, Hendra; Ritonga, Ali Mahadi (CV. Pusdikra Mitra Jaya, 2024)
Imam Al-Ghazali, a highly respected medieval Islamic scholar, has provided insight into various aspects of human life, including buying and selling activities. This paper raises Al-Ghazali's views regarding profit taking in the context of buying and selling. The type of this research is descriptive qualitative research and data sources are obtained from books, scientific papers and the internet. The results of this study are that Al-Ghazali's views are rooted in Islamic teachings which emphasize the importance of honesty, justice and blessing in all aspects of life. In buying and selling activities, Al-Ghazali emphasized that profit taking must be reasonable and not excessive. He rejects practices that harm others or exploit the needs of others to gain an unfair advantage.